1999
DOI: 10.9749/jin.100.199
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Human Escape on Board-III

Abstract: Simulations of human escape on board , taking human factors into consideration , are car − ried out with parameters such as initial allocation of full members of passenger , person types , incident scenarios , and psychological variables . Effects of mass psychology on escape tiIDc are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…To investigate human behaviors in evacuations on inclined ships, researchers from many institutions, including the Korea Research Institute of Ships and Ocean Engineering (KRISO), 26 Netherlands Organization for Applied Scientific Research (TNO), 27 Swiss Federal Institute of Technology in Zurich (ETH), 28 BMT Fleet Technology (BMT), 29 Research Institute of Marine Engineering of Japan (RIME), and Maritime Research Institute of Japan (NMRI), 30,31 Hamburgische Schffbau-Versuchsanstalt (HSVA) 10 and Dalian Maritime University (DMU) 32 have conducted studies based on real data or simulators. Sun et al 33 conducted a series of experiments in which 17 students walked on an inclined corridor simulator with a length of 10.0 m, width of 1.8 m, and height of 2.2 m. The results showed that trim angles have a greater influence on the free and fast walking speed than heeling angles.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate human behaviors in evacuations on inclined ships, researchers from many institutions, including the Korea Research Institute of Ships and Ocean Engineering (KRISO), 26 Netherlands Organization for Applied Scientific Research (TNO), 27 Swiss Federal Institute of Technology in Zurich (ETH), 28 BMT Fleet Technology (BMT), 29 Research Institute of Marine Engineering of Japan (RIME), and Maritime Research Institute of Japan (NMRI), 30,31 Hamburgische Schffbau-Versuchsanstalt (HSVA) 10 and Dalian Maritime University (DMU) 32 have conducted studies based on real data or simulators. Sun et al 33 conducted a series of experiments in which 17 students walked on an inclined corridor simulator with a length of 10.0 m, width of 1.8 m, and height of 2.2 m. The results showed that trim angles have a greater influence on the free and fast walking speed than heeling angles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…36 BMT Fleet Technology conducted relevant experiments on a motion simulator SHEBA, which consists of a corridor model with stairs and a room, and the simulator can be inclined around one axis up to 22°. 29 Katasuhara et al 30,31 from the RIME and NMRI not only reported that the average walking speed of students who participated in their experiment was 1.4 m/s but also designed a device that can change the width of the corridor for inclination tests to study how pedestrians’ speeds influenced by trim and heeling angles. Considering the factors of safety and experimental costs, simulations of ship evacuation have gained popularity, and inclination angles were extended in these simulations.…”
Section: Literature Reviewmentioning
confidence: 99%